Students’ Perception of using Instagram to Vocabulary Mastery in University Muhammadiyah Kalimantan Timur - Danung Cipta Wardana; Dzul Rachman; Ibrahim (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2025)
The integration of social media into education in the contemporary digital era has created novel avenues for engaging students in language acquisition. This research delivers to look at the usage of Instagram as a supplement to promote vocabulary mastery among students at a University Muhammadiyah Kalimantan Timur. Although vocabulary is important in language competency, traditional techniques may fail to engage kids. Instagram, which is frequently used by teenagers for visual communication, gives an opportunity for contextual and interactive vocabulary development. This qualitative descriptive study will involve watching classroom activities and conducting semi-structured interviews to investigate students' involvement, reactions, and vocabulary growth using Instagram-based tasks. The study intends to evaluate the efficacy of Instagram in enhancing vocabulary acquisition, investigate its implementation in the classroom, and comprehend students'perspectives of its utility as an educational resource.